An analysis of the prevalence of peripheral giant cell granuloma and pyogenic granuloma in relation to a dental implant - Nieves Román-Quesada; Beatriz González-Navarro; Keila Izquierdo-Gómez; Enric Jané-Salas; Antonio Marí-Roig; Albert Estrugo-Devesa; José López-López (BMC, 2021)
Abstract Background The aim of the present investigation was to evaluate the literature recurrence of peripheral giant cell granuloma and pyogenic granuloma associated with dental implants. It's important to know the characteristics present in these lesions and possible effects on the prognosis of dental implants. Methods An electronic search without time restrictions was done in the databases: PubMed/Medline. With the keywords "Granuloma" OR "Granuloma, Giant Cell" OR "peripheral giant cell" OR "Granuloma, Pyogenic" AND "Dental implants" OR "Oral implants". Results After applying the inclusion and exclusion criteria, a total of 20 articles were included, which reported 32 lesions (10 pyogenic granulomas, 21 peripheral giant cell granulomas and one peripheral giant cell granuloma combined with peripheral ossifying fibroma, all associated with implants). According to our review, these lesions are more frequent in males and in the posterior region of the mandible. Both excision and curettage of the lesion, compared to only excision, presented similar recurrences (40%). Explantation of the implant was performed in 41% of cases without additional recurrences. The results are not statistically significant when comparing one lesion to the other in terms of explantation (p = 0.97), recurrence (p = 0.57) or bone loss (p = 0.67). Conclusions The main therapeutic approach is tissue excision. The lesions show a high recurrence rate (34.4%), which often requires explantation of the associated implant. This recurrence rate is not affected by curettage after excision.